Interação Trichoderma-feijoeiro e seus efeitos na fisiologia e indução de resistência contra antracnose (Colletotrichum lindemuthianum) - Dildey, Omari Dangelo Forlin (2014)
Biotic inducing agents such as Trichoderma spp. are alternative uses for the resistance induction by activating plants mechanisms of defense. This work aimed to study the interaction of Trichoderma spp different isolates in bean plant on anthracnose control by evaluating the effects on the induction of resistance. Three experiments were conduced, one in vitro and two under greenhouse conditions. In vitro the aggressiveness of 21 Trichoderma isolates was evaluated by the culture direct confrontation method against C. lindemuthianum. In the greenhouse the bean plant was grown and treated with Trichoderma spp. (in vivo assay 1), which was inoculated via seed treatment in sterilized soil. A second assay was conducted which received inoculation from the 21 isolates inoculated via colonized rice deposition in the furrow and foliar spray of exudates of the same isolates. Leaves and roots collections for the enzyme activity determination before the exudates application, after the exudates application and collects after the inoculation were carried out. Analysis of defense enzymes (peroxidase (POX), polyphenol oxidase (PPO), fenilalanina ammonia-lyase (PAL), and β-1,3-glucanase (β-GASE)) was held. To check the endophytic colonization ability of the isolates, fragments of bean plant s roots were sanitized and placed in Petri dishes containing PDA media. The net rate of CO2 assimilation, chlorophyll content and anthracnose s severity on bean plants were also evaluated. The data were subjected to variance analysis and compared by the Scott-Knott test (p <0.05). The isolates TI2, TI4, TLB3, TLB12 (T. harzianum); TI3, TM2 (T. virens); TLB6 (T. asperellum); TLB14, TLB17 (T. koningiopsis) were considered as very efficient and the isolates TI1, TM4, TLB9, TLB15 (T. virens); TLB2, TLB4, TOD1, TOD3 (T. harzianum); TOD2A, TOD2B (T. longibrachiatum) were considered as efficient in direct confrontation against C. lindemuthianum. The isolates of Trichoderma spp, TI2 and TI4 (T. harzianum), TM4, TLB2, TLB9, TLB15, TOD1 (T. virens); TLB17 (T. koningiopsis) colonized the bean plant's roots, giving the microorganism endophytic ability on bean plant s roots. Trichoderma isolates interfere with the bean plant metabolism, acting endophytically. The isolates TI1, TM1, TLB15 (T. virens); TI2, TLB3, TLB4, TLB12, TOD1, TOD3 (T. harzianum); TLB6 (T. asperellum); TLB14, TLB17 (T. koningiopsis); TOD2B (T longibrachiatum) suppressed the β-1,3-glucanase activity in the leaf tissue, being considered as suppressors for the induction of defense on bean plants. The defense enzymes activity on the resistance induction of the bean plant treated with Trichoderma spp. for protection against C. lindemuthianum showed no major changes. The isolates did not affect the net rate of CO2 assimilation and did not change the chlorophyll content. The incidence of anthracnose's severity on bean plants, showed no significant difference by treatment via seed/soil and foliar spray of the exudates on the interaction of Trichoderma spp. evaluated. However the management with Trichoderma spp. cannot be ruled out and requires further studies in this pathossystem